The role of investment banking for the German economy: Final report for Deutsche Bank AG, Frankfurt/Main - Michael Schröder; Mariela Borell; Reint E. Gropp; Zwetelina Iliewa; Lena Jaroszek; Gunnar Lang; Sandra Schmidt; Karl Trela (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
The aim of this study is to assess the contributions of investment banking to the economy with a particular focus on the German economy. To this end we analyse both the economic benefits and the costs stemming from investment banking. The study focuses on investment banks as this part of banking is particularly relevant for financing companies as well as the development and use of specific products to support the needs of private and professional clients. The assessment of benefits and costs of investment banking has been conducted from a European perspective. Nevertheless there is a focus on the German economy to allow a more detailed analysis of certain aspects as for example the use of derivatives by German companies, the success of M&As in Germany or the effect of securitization on loan supply and GDP in Germany. For comparison purposes other European countries and also the U.S. have been taken into account. The last financial crisis has shown the negative impacts of banks on the financial system and the whole economy. In a study on the contribution of investment banks to systemic risk we quantify the negative side of the investment banking business. In the last part of the study we assess how the effects of regulatory changes on investment banking. All important changes in banking and capital market regulation are taken into account such as Basel III, additional capital requirements for systemically important financial institutions, regulation of OTC derivatives and specific taxes.
Keywords: 330; Investmentbank; Kosten-Nutzen-Analyse; Deutschland